Innowacje instrumentem zarządzania przedsiębiorstwem - Baruk, Jerzy (Innovations as an Instrument in Enterprise Management, 2006)
In this article three essential issues are discussed: 1) innovation essence and its features. The author proposed own definition of an innovation and presented its common characteristics, 2) combining entrepreneurship and innovation, 3) ability of enterprise to introducing innovations - the results of the empirical researches.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 19-26